Rest for the Restless?: Karl Rahner, Being, and the Evocation of Transcendence - Sanders, Theresa (Philosophy & theology, 1994)
In Spirit in the World, Karl Rahner contends that the existence of an Absolute Being is affirmed. However, such an affirmation is beyond the scope of his own methodology. Since the questions that characterize the philosophical theology of Rahner are also those that occupy postmodern thought (structures of knowing, the status of ontology, and the constitution of the subject) , this essay attempts ta read Rahner through the insights of philosophers such as Derrida and Taylor. The thesis is that Rahner’s method does not lead to Absolute Being; rather, God can be understaod as the restlessness that drives the human heart.